Building Information Modeling Applications in Energy-Efficient Refurbishment of Existing Building Stock: A Case Study - Yildirim, Muhammed; Polat, Hasan (Mdpi, 2023)
The built environment contributes to 35% of the global energy consumption and 38% of energy-related carbon emissions. The exponential population growth, coupled with the inability of the existing building stock to meet demands or reach the end of its lifespan, has precipitated the proliferation of new constructions worldwide. However, it has been proven well that retrofitting existing buildings might impact the environment less, save resources, and reduce the carbon footprint while extending their lifecycle. Various techniques are available to assess the performance of existing buildings and quantify the energy-saving potential of renovation measures. Building information modeling (BIM) technology serves as a virtual laboratory for buildings and can be used to model building stocks and measure how building performance changes with alternative envelope and system proposals. This research study explores the potential of BIM-based energy modeling to evaluate the effectiveness of refurbishment scenarios on a residential building. A total of 192 alternative scenarios were developed by considering six variables (wall, roofing, insulation, glazing, lighting power density, and photovoltaic panels). The results were analyzed across annual energy consumption (fuel and electric), annual/lifecycle energy costs, energy use intensity, annual CO2 emissions, and initial investment costs. The optimum alternative scenario decreased the annual fuel and electricity consumption of the sample building by 61% and 64%, respectively. The payback period was calculated as 12 years. This study demonstrates the impact of BIM in enhancing the energy efficiency of the existing building stock, presenting results within the context of a residential building.
Keywords: building information modeling; retrofit; residential buildings; sustainability; energy performance; simulation